2022
DOI: 10.1038/s41378-022-00419-6
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasensitive and stretchable strain sensor based on a microcrack structure for motion monitoring

Abstract: Flexible strain sensors are promising candidates for intelligent wearable devices. Among previous studies, although crack-based sensors have attracted a lot of attention due to their ultrahigh sensitivity, large strain usually causes fractures in the conductive paths. Because of the unstable crack structure, the tradeoff between sensitivity and workable strain range is still a challenge. As carbon nanotubes (CNTs) and silver nanowires (AgNWs) can form a strong interface with the thermoplastic substrate and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The improvements in GF may be explained by the existence of percolated CNC nanostructures in the eutectogel nanocomposites. [ 4–6 ] The percolated CNC network could have been altered when the nanocomposites were stretched, thereby yielding more pronounced changes in the electrical resistance of the nanocomposites when subjected to different strains as compared to the pristine eutectogel. As all the systems developed in this study displayed high sensitivity to mechanical deformation ( Figure a), these preliminary results suggested the promise of all‐natural and transient eutectogel nanocomposites as strain sensors for wearable electronics applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvements in GF may be explained by the existence of percolated CNC nanostructures in the eutectogel nanocomposites. [ 4–6 ] The percolated CNC network could have been altered when the nanocomposites were stretched, thereby yielding more pronounced changes in the electrical resistance of the nanocomposites when subjected to different strains as compared to the pristine eutectogel. As all the systems developed in this study displayed high sensitivity to mechanical deformation ( Figure a), these preliminary results suggested the promise of all‐natural and transient eutectogel nanocomposites as strain sensors for wearable electronics applications.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2,3 ] Conventional wearable strain sensors consist of percolated elastomer‐conductive filler composites that transduce mechanical deformations into variations in electrical resistance. [ 4–6 ] However, percolated networks are susceptible to structural damage at large strain, causing irreversible losses in electrical properties and in sensing functions (operation generally limited to strain ranging from 0 to 100%). [ 6 ] Meanwhile, the sustained use of non‐biodegradable polymers and nanofillers has caused the accumulation of electronic waste (e‐waste) in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although crack-based sensors have attracted a lot of attention due to their ultrahigh sensitivity, the trade-off between sensitivity and workable strain range is still a challenge due to the unstable crack structure. , Sensors with bioinspired interlocked macrodome arrays can overcome this change since it is very sensitive both to pressure and strain. , With this idea in mind, a wearable electronic device with interlocked macrodome arrays containing a microcrack structure is assembled for vibratory monitoring (Figure a,b) . Conductive silver paste is first 3D printed onto the SUBI-PDMS substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[8] In contrast, wearable strain sensors composed of various soft and robust materials, such as Ecoflex, Dragon Skin, poly(styrene-ethylene-butylene-styrene) (SEBS), and thermoplastic polyurethane, have a dynamic strain range considerably larger than 100%, which can be used for on-body strain monitoring. [9][10][11][12] Some studies on material science at micro and nanoscales toward wearable applications have shown significant advances in terms of sensitivity, response time, dynamic working range, etc. [13][14][15][16][17] In spite of the substantial efforts toward such developments, conventional studies on wearable strain sensors are limited by highly complicated fabrication and high-cost material synthesis.…”
Section: Introductionmentioning
confidence: 99%